Patients with a Previous History of Malignancy Undergoing Lung Cancer Screening: Clinical Characteristics and Radiologic Findings. Issue 9 (September 2016) - Halpenny, Darragh F.; Cunningham, Jane D.; Long, Niamh M.; Sosa, Ramon E.; Ginsberg, Michelle S.
ABSTRACT : Introduction: : The aim of this study was to describe the clinical characteristics and radiologic findings in patients with a previous history of malignancy who underwent computed tomography (CT) screening for lung cancer. Methods: : Patients with a previous history of malignancy and a life expectancy of at least 5 years who were referred for lung cancer screening between May 2, 2011, and September 24, 2014, were included. CT scan features assessed included nodule size, morphologic features, and number. The Lung‐CT Reporting and Data System scoring system was retrospectively applied to all studies. Results: : A total of 139 patients were studied (mean age of 66 years and median smoking history of 50 pack‐years). All had a previous history of cancer, most often breast cancer (60 patients [43%]), head or neck cancer (26 patients [19%]), and lung cancer (16 patients [12%]). Of these patients, 42 (30%) had a positive screening study result. Lung cancer was diagnosed in seven patients (5%), and a radiation‐induced chest wall sarcoma was diagnosed in one patient (1%); 42 patients (30%) had a positive chest CT scan per the National Comprehensive Cancer Network lung cancer screening nodule follow‐up algorithm. Conclusion: : The rate of diagnosis of lung cancer in our patient population is higher than in several previously published studies. Smokers with a history of malignancy may be a group at particularly high risk for the development of subsequent lung cancer.